Chiglitazar ameliorates dehydroepiandrosterone-induced polycystic ovary syndrome in rats - Fuzhen Zhao; Wei Cui; Chengmei Fang; Yuanyuan Luo; Cheng Zhang (Journal of Ovarian Research)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine and metabolic disorder accompanied by ovulatory dysfunction. Insulin resistance (IR) is a key pathogenic mechanism in PCOS, and insulin sensitizers, such as metformin and pioglitazone, can improve PCOS symptoms. Chiglitazar, a pan-peroxisome proliferator-activated receptor (pan-PPAR) agonist, is also an insulin sensitizer; however, its therapeutic effects have not yet been studied in PCOS. We evaluated the therapeutic effects of chiglitazar in a rat model of PCOS. Methods Sprague–Dawley rats aged 4 weeks were injected subcutaneously with dehydroepiandrosterone (DHEA) (6 mg/100 g/day) to establish PCOS, and a control (CON) group was established. The rats were divided into the CON, PCOS model (DHEA), pioglitazone-treated (DHEA + PIO), and chiglitazar-treated (DHEA + CHI) groups. The DHEA + PIO group received pioglitazone (20 mg/kg/day) and the DHEA + CHI group received chiglitazar (20 mg/kg/day), each for 15 days. Body weight, estrous cycle, and glucose tolerance test (GTT) and insulin resistance test (ITT) results were monitored. Experimental animal energy metabolism systems were utilized to assess metabolic parameters. Enzyme-linked immunosorbent assay was conducted to detect changes in serum hormones, including insulin, adiponectin, sex-related hormones, and lipid metabolism indicators. The ovaries were used for molecular biology experiments to detect changes in Akt/phosphorylated Akt and glucose transporter 4 (GLUT4) expression by Western blotting and quantitative polymerase chain reaction. Results Chiglitazar and pioglitazone improved PCOS symptoms. However, chiglitazar demonstrated a more pronounced effect on lipid improvement and weight gain than pioglitazone. In the DHEA + PIO and DHEA + CHI groups, there was notable recovery in oxygen consumption and carbon dioxide output; substantial improvement in GTT and ITT results; an increase in adiponectin; and a reduction in serum insulin, androgens, luteinizing hormone (LH), and LH/follicle-stimulating hormone ratio. Compared with the DHEA group, the DHEA + CHI group exhibited notable decreases in triglycerides, free fatty acids, and atherosclerosis index, while the DHEA + PIO group demonstrated no changes. Granulosa cells and healthy follicles increased in ovarian sections. Ovarian steroidogenic enzymes also increased in the DHEA + PIO and DHEA + CHI groups compared with the DHEA group. Mechanistically, chiglitazar increased Akt phosphorylation. Conclusion Chiglitazar significantly improved ovulation in rats with PCOS and may be a potential novel therapeutic strategy for PCOS.